Analysis Of Factors Related To Stunting In Toddlers Aged 25-59 Months In Puspasari Village, Puspahiyang, Tasikmalaya 2019 - Risza Choirunnisa; Triana Indrayani; Fitri Latipatul Anshor (Universitas STRADA Indonesia, 2020)
Research design used in this research is quantitative with cross sectional design. The population of this research is toddlers aged 25-59 months. The research uses simple random with 74 toddlers aged 25-59 month as the sample at Puspasari Village. The instrument used is questionnaire.The prevalence of stunting toddlers Puspasari Village is 22, 3%. The frequency of LBW history is (12.2%), without exclusive breastfeeding is (8, 1%), less knowledgeable about complementary feeding is (28, 4%), unhealthy sanitation is (79, 7%), and low family income is (86, 5%). There is no significant relation of LBW (p value=0,596, OR=0,686) and exclusive breastfeeding (p value=0,890, OR=0,889) with stunting. There is a significant relation of the knowledge of mother about complementary feeding (p value=0,000, OR=9,143), sanitation (p value=0,004, OR=6,261), family income (p value=0,026, OR=5,481) with stunting